The Anti-Biofilm Potential of Linalool, a Major Compound from Hedychium larsenii, against Streptococcus pyogenes and Its Toxicity Assessment in Danio rerio - Sarath Praseetha; Swapna Thacheril Sukumaran; Mathew Dan; Akshaya Rani Augustus; Shunmugiah Karutha Pandian; Shiburaj Sugathan (MDPI AG, 2023)
The anti-biofilm and anti-virulence potential of the essential oil (E.O.) extracted from Hedychium larsenii M. Dan & Sathish was determined against Streptococcus pyogenes. A crystal violet assay was employed to quantify the biofilm. Linalool, a monoterpene alcohol from the E.O., showed concentration-dependent biofilm inhibition, with a maximum of 91% at a concentration of 0.004% (v/v). The AlamarBlueTM assay also confirmed Linalool's non-bactericidal anti-biofilm efficacy (0.004%). Linalool treatment impeded micro-colony formation, mature biofilm architecture, surface coverage, and biofilm thickness and impaired cell surface hydrophobicity and EPS production. Cysteine protease synthesis was quantified using the Azocasein assay, and Linalool treatment augmented its production. This suggests that Linalool destabilizes the biofilm matrix. It altered the expression of core regulons covRS, mga, srv, and ropB, and genes associated with virulence and biofilm formation, such as speB, dltA, slo, hasA, and ciaH, as revealed by qPCR analysis. Cytotoxicity analysis using human kidney cells (HEK) and the histopathological analysis in Danio rerio proved Linalool to be a druggable molecule against the biofilms formed by S. pyogenes. This is the first report on Linalool's anti-biofilm and anti-virulence potential against S. pyogenes.